The Problem of Violence in Mainländer’s Worldview - Baquedano, Sandra (2021)
“The Problem of Violence in Mainländer’s Worldview”. Is it possible for a philosopher to, by example, promote violence as a means of conflict resolution? Socrates, Descartes, Rawls, Wittgenstein or Jonas, among others, are cases of those who ended up for different reasons enlisting in armies or participating in some way in various wars or conflicts. Despite this, many managed not to mix their philosophies with something alien to it. This article aims to investigate Mainländer’s The Philosophy of Redemption in order to detect the dangers of exalting the use of violence, by elevating love of the country to the level of philosophical wisdom. This aspect will be identified as the most critical of his thinking and will explain why he isn’t qualified as a philosopher in this paper, but referred to as a thinker. This is sustained to the extent that certain reflections that turn out to be essential in some matters could end up being contaminated by a nationalist fanaticism, opening the possibility of thinking about a base of crypto-bellicism in some aspects of his work.